Financial ratio analysis to assess financial performance village owned enterprises (Bumdes Barokah) Mlaras Village Sumobito District Jombang Regency - Lavenia; Safari, Dedy Eko T.; Supriadi, Supriadi; Istikomah, Lilik (Institute of Computer Science (IOCS), 2024)
An organization's financial performance can be assessed by looking at the results of the financial reports made each period. Financial analysis is not only seen from financial reports but can also be seen from financial ratio analysis. This research aims to determine the financial performance of Village-Owned Enterprises (BUMDes) in Mlaras Village, Sumobito District, Jombang Regency for the 2018 to 2020 fiscal year. The data for this research is the financial report of BUMDes Barokah for 2018-2020. The research results show that (1) the liquidity ratio is good and very liquid because there are no current debts, (2) the solvency ratio is very good because in carrying out its business it uses capital optimally, (3) the profitability ratio is very good by using capital and generating opinions and profits which is optimal, and (4) the activity ratio is very good, indicating that all assets can be used optimally.